ASPECTOS COMUNICATIVOS E CULTURAIS NOS HÁBITOS CULINÁRIOS CAIÇARA DA COMUNIDADE QUILOMBOLA DA FAZENDA PICINGUABA, DE UBATUBA SP - Paravati, Luís Carlos (2014)
Study about the communicative processes involved in the quilombola community from Fazenda Picinguaba de Ubatuba, SP culinary habits transformation. Its objective is to understand the origins and causes that provoked the Quilombo da Fazenda community culinary habits changes, using a comparative analysis between primitive and current doings. The communication process developed to transmit the feeding culture between generations was also analyzed, identifying the languages used. As an instrument to understand these phenomena, this research was carried at the light of cultural studies theories and concepts; of concepts about communities and identities, and also the folkcommunication theory developed by Luiz Beltrão. For such, bibliographic research and document studies were performed, and also interviews using the oral history method with community members. The results obtained indicate a change in Quilombo da Fazenda community feeding habits, due to ease the of access to food commerce provided by both the Rio-Santos highway construction and the influence brought by television, with the implantation of electric energy in 2008. However, we observe that, in spite of these changes, the quilombola feeding culture basis keeps many of its original aspects. The communication inside the quilombola community and the traditional knowledge and doing transfer occur mostly orally. We identify the presence of dancing, music, conversation circle, culinary, craftsmanship that correspond to the folkcommunication genre.